Exploring Deposition Techniques and Supramolecular Arrangement in Thin Films for Sensor Applications - Miyazaki, Celina M. [UNESP] (2023)
In recent decades, many research efforts have been dedicated to finding highly sensitive devices for fast and reliable identification and quantification of an expanding range of analytes. As a result, there has been an increased number of publications dedicated to this area and a consequent increase in the number of review papers on the subject. However, unlike most review articles, we chose to explore the impact of supramolecular arrangement (or deeper, when possible, approaching the molecular organization) and assembly variables on sensing performance. This review briefly discusses the methods used to determine the molecular organization of thin films. We also examine various deposition techniques, including Langmuir-Blodgett, Langmuir-Schaefer, Layer-by-Layer assembly, electrodeposition, and spray pyrolysis, describing mainly (but not limited to) the advances in the last five years in developing thin films for sensors, with a particular emphasis on how the supramolecular arrangement can influence the sensing properties of these films.